METHOD OF EDUCATING WITH HEART ON STUDENT CHARACTER FORMATION AT MTS NURUL IMAN MODONG TANAH ABANG DISTRICT PALI REGENCY - Zaimmuddin Zaimmuddin; Fitriana Fitriana; Apriyanti Apriyanti (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aimed to provide an overview of the implementation of the method of educating with heart on student character formation at MTS Nurul Iman Modong, Tanah Abang District, Pali. The research method used was a qualitative method. Data were taken through observation and interviews. Respondents consisted of 20 students of grade 3 of Mts Nurul Iman Modong. The data obtained from observation and interview were then analyzed by using interactive analysis through several components, namely data collection, data reduction, data presentation, and drawing conclusions. The learning used in this research was the method of educating by heart. This study provided illustration that, through the concept of educating with heart can lead to a good, have moral and character generations.